Tecnologias assistivas como ferramentas de inclusão educacional: um estudo prospectivo de tecnologias protegidas - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Hearing and visual impairments hinder the ability to perform daily tasks, and it is necessary to identify alternative ways for people with disabilities to carry out their activities independently. Assistive Technology, as an interdisciplinary area of knowledge, offers resources and services, and makes the paradigm of social inclusion possible. This study conducted a prospective study through patents, scientific publications, records, search sites to identify educational assistive technologies for students with hearing and visual impairments. This research also mapped assistive technologies that are being used by federal higher education institutions, which are focal points of PROFNIT. The results of this study indicate that Ifes contribute to the production of Assistive Technology in the national scenario, being the largest depositors, but that the government needs to invest more in promoting Assistive Technology for people with hearing and visual impairments. It is concluded that all the mapped Ifes have an accessibility center and have Assistive Technology to assist students with hearing and visual impairments in undergraduate courses.
Keywords: Tecnologia Assistiva; Deficiência Visual; Deficiência Auditiva; CNPQ:: EDUCAÇÃO